1997
DOI: 10.1177/002224299706100205
|View full text |Cite
|
Sign up to set email alerts
|

Film Critics: Influencers or Predictors?

Abstract: Critics and their reviews pervade many industries and are particularly important in the entertainment industry. Few marketing scholars, however, have considered the relationship between the market performance of entertainment services and the role of critics. The authors do so here. They show empirically that critical reviews correlate with late and cumulative box office receipts but do not have a significant correlation with early box office receipts. Although still far from any definitive conclusion, this fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
261
2
12

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 535 publications
(306 citation statements)
references
References 20 publications
11
261
2
12
Order By: Relevance
“…Burzynski and Bayer (1977) found that if audiences receive negative information about a movie before watching it, their evaluation of it is hampered (Wyatt and Badger, 1984). Focusing on market-level responses to reviews, Eliashberg and Shugan (1997) found that rating valence plays a significant role in forecasting movie sales. Basuroy et al (2003) found that rating valance is significantly associated with initial sales.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Burzynski and Bayer (1977) found that if audiences receive negative information about a movie before watching it, their evaluation of it is hampered (Wyatt and Badger, 1984). Focusing on market-level responses to reviews, Eliashberg and Shugan (1997) found that rating valence plays a significant role in forecasting movie sales. Basuroy et al (2003) found that rating valance is significantly associated with initial sales.…”
Section: Literature Reviewmentioning
confidence: 99%
“….35 counting for an explained variance of less than 10%. This significant but weak role of expert judgment has appeared repeatedly when explaining the popular appeal or market success of the arts or of entertainment in general (Hirschman and Pieros 1985;Holbrook 2006;Luan and Sudhir 2005;Reddy, Swaminathan, and Motley 1998;Schindler, Holbrook, and Greenleaf 1989) and has recurred especially in the often-studied case of motion pictures in particular (Basuroy, Chatterjee, and Ravid 2003;Basuroy, Desai, and Talukdar 2006;Boatwright, Kamakura, and Basuroy 2005;Dellarocas, Awad, and Zhang 2004;Desai and Basuroy 2005;Elberse and Anand 2005;Eliashberg and Shugan 1997;Hennig-Thurau, Houston, and Walsh 2003;Holbrook 1999;Kamakura, Basuroy, and Boatwright 2006;Litman 1983;Litman and Ahn 1998;Prag and Casavant 1994;Ravid 1999;Ravid, Wald, and Basuroy 2005;Reinstein and Snyder 2005;Sawhney and Eliashberg 1996;Sochay 1994;Wallace, Seigerman, and Holbrook 1993;Zufryden 2000).…”
mentioning
confidence: 99%
“…For example, in studying motion pictures, it could happen that marketing efforts such as production budgets, advertising, or distribution strategy influence expert judgment, ordinary evaluation, or popular appeal. Further, some have argued that movie reviewers anticipate audience acceptance and thereby reflect, rather than influence, market success (Eliashberg and Shugan 1997). Also, people cannot evaluate a film until after they have seen it, from which it follows that theatrical box office receipts or video rentals might drive ordinary evaluation or popular appeal rather than the other way around.…”
mentioning
confidence: 99%
“…The influence of negative reviews, however, was less than that of positive reviews, and, moreover, diminished faster. Eliashberg and Shugan (1997) reported critics' reviews were insignificant in the short run, but significant cumulatively and with later box office receipts. Copernicus Market Consulting (Clancy, 2000) asserted that movie critics' reviews had no impact on box office success.…”
mentioning
confidence: 94%